Nitrogen fertilizer management for maize production under tropical climate - Lucas, Fábio Teixeira [UNESP]; Borges, Bernardo Melo Montes Nogueira [UNESP]; Coutinho, Edson Luiz Mendes [UNESP] (Wiley, 2019)
High maize (Zea mays, L.) yields require an adequate supply of N fertilizer. As an alternative, fertilizers with nitrification and urease inhibitors have emerged onto the market to increase N supply to crops. The objective of this study was to determine the effects of urea treated with nitrification and urease inhibitors on plant growth and grain yield. The experiment was performed in a weathered tropical soil, in the 2013/2014 and 2014/2015 crop seasons. Fertilizer treatments were four N levels (0, 50, 100, and 200 kg ha–1 N); three urea treatments (urea with urease inhibitor: [N-(N-butyl) thiophosphoric triamide]–NBPT; urea with nitrification inhibitor: (3,4-dimethylpyrazole-phosphate)– DMPP; and conventional urea) and two application strategies (total N applied at sowing; and 30 kg ha–1 N at sowing and the remainder topdressed once plants had four completely developed leaves). Critical levels for chlorophyll index (CI), leaf N concentration, leaf area index (LAI), and N levels were 52.7, 27.5 g kg–1, 4.3 m2 m–2 and 110 kg ha–1, respectively. Addition of inhibitors and split N application did not increase growth, nutrition or yield compared to conventional urea and total N applied at sowing. However, increase of N levels increased grain yield by up to 185 kg ha–1 N. On the other hand, agronomic N use efficiency linearly decreased as N levels increased. It can be concluded that N sources and application strategies were not significant factors in grain yield. Therefore, N from conventional urea might be applied solely at sowing.